2009
DOI: 10.1186/1475-2875-8-21
|View full text |Cite
|
Sign up to set email alerts
|

Malaria and water resource development: the case of Gilgel-Gibe hydroelectric dam in Ethiopia

Abstract: Background: Ethiopia plans to increase its electricity power supply by five-fold over the next five years to fulfill the needs of its people and support the economic growth based on large hydropower dams. Building large dams for hydropower generation may increase the transmission of malaria since they transform ecosystems and create new vector breeding habitats. The aim of this study was to assess the effects of Gilgel-Gibe hydroelectric dam in Ethiopia on malaria transmission and changing levels of prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
98
2
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(114 citation statements)
references
References 30 publications
9
98
2
3
Order By: Relevance
“…Some studies have shown no impact of hydroelectric dam construction on nearby malaria (68), but most show an increase in risk (112,122,234 Policy on dams needs to balance the considerable health benefits of available energy and water management with local adverse health and social impacts (127,131,230). For this purpose, guidelines have been issued for equitable, atraumatic resettlement (229).…”
Section: Wwwannualreviewsorg • Energy and Human Healthmentioning
confidence: 99%
“…Some studies have shown no impact of hydroelectric dam construction on nearby malaria (68), but most show an increase in risk (112,122,234 Policy on dams needs to balance the considerable health benefits of available energy and water management with local adverse health and social impacts (127,131,230). For this purpose, guidelines have been issued for equitable, atraumatic resettlement (229).…”
Section: Wwwannualreviewsorg • Energy and Human Healthmentioning
confidence: 99%
“…For example, the construction of the Koka dam was also associated with increased levels of malaria transmission and with P. falciparum becoming more prevalent in communities adjacent to the dam site 55 . Similarly, YEWHALAW et al 101 observed a higher proportion of P. vivax infections on children living in communities near the Gilgel-Gibe dam, but the proportions of P. falciparum cases were not significantly different for at-risk communities and villages farther away. Finally, transmission enhancement was also verified in communities close to the Bamendjin dam in Cameroon 3 .…”
Section: Africamentioning
confidence: 88%
“…when people are moved from fertile rural areas to cities (Wilmsen et al 2011 ), and most often results in the impoverishment of affected households (Scudder 2005 ). Flow regulation for hydroelectric production can negatively affect downstream agricultural lands (Kuenzer et al 2013 ) and fi sheries (Silvano et al 2009 ), while the creation of hydroelectric reservoirs can have negative health implications in some areas (Yewhalaw et al 2009 ). Nevertheless, we will not further discuss these global climate and social issues here and will henceforth focus on the ecological impacts of hydroelectric production on aquatic systems and their biota.…”
Section: Hydroelectric Production Infrastructures: Overviewmentioning
confidence: 99%